Impact of the COVID-19 pandemic on the activities of the gymnastics academies (Research, Society and Development, 2022)
This study sought to understand the situation of gyms during the COVID-19 pandemic, through analysis of reports from a widely circulated website. It was observed about the context of the closing and damage of the gyms; client, company and professional relationship; consequences in the entrepreneurial environment of the fitness area; strategies employed by professionals in the field and gradual reopening. After analyzing the 246 selected reports, it was identified that São Paulo and Minas Gerais were the most reported states, which may be related to the fact that they belong to the region with the highest flow of news in the country. Some of the alternatives used by the academies were the negotiation of the months of tuition paid as credit for the post-isolation period, while others decided to suspend the payment of tuition until the isolation was relaxed. They also used online service, home service, equipment loan and individual service at the establishment as an alternative. Despite the proposal of these alternatives, in general, the suspension of face-to-face activities caused financial losses. Therefore, it is considered that the process of recovering lost billing will be slow.